2013
DOI: 10.3758/s13421-013-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

How similar are recognition memory and inductive reasoning?

Abstract: Conventionally, memory and reasoning are seen as different types of cognitive activities driven by different processes. In two experiments, we challenged this view by examining the relationship between recognition memory and inductive reasoning involving multiple forms of similarity. A common study set (members of a conjunctive category) was followed by a test set containing old and new category members, as well as items that matched the study set on only one dimension. The study and test sets were presented u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Behavioral studies showed that induction can be varied with different properties (Hayes and Heit, 2013;Heit and Rubinstein, 1994). For example, Hayes and Heit (2013) compared the inductions based on aquatic mammal premises with three kinds of properties: a blank property (a newly discovered property X), a habitat property (a newly discovered enzyme to assist in the development of a water-resistant body covering) and a mammal property (a newly discovered enzyme in breast milk that is passed to the young during feeding); they found that participants made more positive responses to aquatic non-mammals in the habitat property than in the blank property, and made more positive responses to land mammals in the mammal property than in the blank property. Based on these findings, it is reasonable to infer that meaningful property violations can increase the amount of semantic content violations, which in turn can influence the N2-P3b-N400 effects.…”
Section: Limitations and Further Studiesmentioning
confidence: 99%
“…Behavioral studies showed that induction can be varied with different properties (Hayes and Heit, 2013;Heit and Rubinstein, 1994). For example, Hayes and Heit (2013) compared the inductions based on aquatic mammal premises with three kinds of properties: a blank property (a newly discovered property X), a habitat property (a newly discovered enzyme to assist in the development of a water-resistant body covering) and a mammal property (a newly discovered enzyme in breast milk that is passed to the young during feeding); they found that participants made more positive responses to aquatic non-mammals in the habitat property than in the blank property, and made more positive responses to land mammals in the mammal property than in the blank property. Based on these findings, it is reasonable to infer that meaningful property violations can increase the amount of semantic content violations, which in turn can influence the N2-P3b-N400 effects.…”
Section: Limitations and Further Studiesmentioning
confidence: 99%
“…Rather, we examined whether cues are used differently for party identification and for voting, and differently for high‐ versus low‐knowledge voters, and differently for Democrats versus Republicans. It is known from laboratory experiments that cue weights are influenced by the task (e.g., Hayes & Heit, ; Nosofsky, ); here the novel question is how do cue weights vary for different political judgments. Likewise it is known that cue weights for biological categorization and reasoning depend on expertise (e.g., Medin & Atran, ; Medin, Lynch, Coley, & Atran, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decisions in each task (whether the test item has been seen before; whether the test item shares a property with the study set) could be seen as driven by an assessment of the similarity between the test probe and the retrieved sample. These hypothesized parallels have been supported in studies comparing induction and recognition responses to a common set of study and test items (Hayes & Heit, 2013a;Hayes, Fritz, & Heit, 2013;Heit & Hayes, 2011). Notably, these same studies also revealed a reliable empirical difference between the two tasksnamely, that induction leads to higher rates of positive responding to novel test items than recognition.…”
mentioning
confidence: 74%